Demonstrating Technique to Teach Vocabulary Viewed From Student Intelligence - Muhammad Husnu (VELES Voices of English Language Education Society, 2017)
This research was aimed at finding out whether: (1) demonstrating technique was more effective than translation technique to teach vocabulary; (2) the students who had high intelligence have better vocabulary than those who had low intelligence; and (3) there was an interaction between teaching techniques and intelligence for teaching vocabulary. Designed as experimental study, it was conducted at the fourth grade of SDN 3 Pancor.  The population of the research was the fourth grade students of SDN 3 Pancor in the academic year of 2015-2016. The samples were two classes. A cluster random sampling technique was used to take the samples. Each class was divided into two groups (the students who have high and low intelligence). Then, the techniques used to collect the data were an intelligence test and a multiple choice test. The vocabulary instruments were tried out to get valid and reliable items. The data were analyzed by using multifactor analysis of ANOVA 2x2 and Turkey test. Based on the findings, it can be concluded that in general demonstrating technique was more effective than translation technique to teach vocabulary. For the students who had high or low intelligence, demonstrating technique was more effective than translation technique to teach vocabulary. In accordance with the above result, the English teacher was expected to be able to select the appropriate teaching technique to teach vocabulary for the students who had high or low intelligence.